Assessment of the handwriting quality: An instrument for the brazilian educational context - Milani, Adriane Guzman Pasculli [UNESP]; Hiraga, Cynthia Yukiko [UNESP]; Pellegrini, Ana Maria [UNESP] (My University, 2018)
Handwriting is a complex skill exclusive to the human being. It is indispensable for the individual to integrate and adapt to our social environment. It is a complex skill that involves a combination of perceptual, motor, kinesthetic, and cognitive components. The assessment of handwriting is one of the challenges encountered by teachers who work with the literacy process. This chapter presents the Minnesota Handwriting Assessment (MHA), an instrument developed by Judith Reisman and used in English speaking language countries, as a possible tool for assessing the quality of the handwriting in the Brazilian educational context. Such an instrument allows us to determine the quality of each child's handwriting objectively, as well as to evaluate the progress of these children and the class as a whole. The results per variable of the quality of the handwriting could provide teachers valuable information regarding the sensory-motor abilities involved in the production of the handwriting.
Keywords: Assessment; Children; Handwriting